The Effects of General Anesthesia on Obese Patients during Surgical Operations - Shamsi , Afzal; Hamidi , Mahsa; Malek , Masoumeh; Salih , Lamyaa Mahdi (Journal of Science in Medicine and Life, 2025)
Background: The condition known as obesity is marked by too much body fat compromising health. Aims: Assessment the effects of general anesthesia on obese patients during surgical operations. Methods: Patients hospitalized in Tehran's special care department of Tehran University of Medical Sciences hospitals (Shariati Hospital and Imam Khomeini Hospital) who fit the criteria for joining the study during 2024–2025 will be the cross-sectional study subjects. Patients will find themselves in the operation room. The IV line is set and normal saline serum is injected to all patients. The patient's body mass index registered at thirty or above. Data were gathered on a researcher-made questionnaire. Descriptive and inferential statistical tests as well as SPSS version 25 program were used in data analysis. Considered noteworthy was a P-value less than 0.05. Results: Reaching 72.5%, the difficult intubation group had the highest percentage of participants intubated based on BMI. Though 27.5% of the participants showed low proportion of easy intubation. At 30-34.9 kg/mm¹ the mean systolic pressure was 127.7 ± 5.98; at 35-39.9 kg/mm¹ the mean systolic pressure was 135.04 ± 9.1. Furthermore, the group of persons with high body mass index had an average diastolic blood pressure greater. Comparatively to heart rate (77.4±6.56) following GA, heart rate (90.7±5.18) before GA of 30-34.9 kg/mm¹ revealed notable (p<0.05) variations. Heart rate (95.18±7.35) before GA exhibited notable (p<0.05) variations in the 35-39.9 kg/mm¹ group as compared to heart rate (84.4±2.42) following GA. Comparatively to oxygen saturation (99.84±0.1) after GA, oxygen saturation (99.94±0.1) before GA of 30-34.9 kg/mm¹ revealed non-significant (p<0.05) variations. Oxygen saturation (99.81±0.09) before GA indicated non-significant (p<0.05) differences in the 35-39.9 kg/mm¹ group as compared to oxygen saturation (99.74±0.13) following GA. Conclusion: Finally, this research showed that individuals who were heavier had greater heart rates, blood oxygen levels, and systolic and diastolic blood pressure. Patients' systolic and diastolic blood pressure, heart rate, and blood oxygen levels did not differ statistically before and after general anesthesia.